Entrepreneurship in the UK - David G. Blanchflower; Chris Shadforth (Institute for the Study of Labor (IZA), 2007)
This paper examines the causes and consequences of changes in the incidence of entrepreneurship in the UK. Self-employment as a proportion of total employment is high by international standards in the United Kingdom, but the share has fluctuated over time. We examine the time series movements in self-employment, which are dominantly driven by financial liberalisation and changes in taxation rules, especially as they relate to the construction sector which is the dominant sector. We document that the median earnings of the self-employed is less than for employees. We show that in comparison with employees the self-employed are more likely to be male; immigrants; work in construction or financial activities; hold an apprenticeship; work in London; work long hours; have high levels of job satisfaction and happiness. Consistent with the existence of capital constraints on potential and actual entrepreneurs, the estimates imply that the probability of self-employment depends positively upon whether the individual ever received an inheritance or gift. Evidence is also found that rising house prices have increased the self-employment rate. There appears to be no evidence that changes in self-employment are correlated with changes in real GDP, nor national happiness.
urn:nbn:de:101:1-20080401126
Keywords: 330; Selbstständige; Unternehmer; Deregulierung; Großbritannien